Luminescence of LiF Crystals Doped with Metal Oxide Impurities; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Korepanov V. I. Vladimir Ivanovich (Optical Technology, 2016)
Title screen